2005
DOI: 10.1086/428890
|View full text |Cite
|
Sign up to set email alerts
|

A Map of the Universe

Abstract: We have produced a new conformal map of the universe illustrating recent discoveries, ranging from Kuiper Belt objects in the solar system to the galaxies and quasars from the Sloan Digital Sky Survey. This map projection, based on the logarithm map of the complex plane, preserves shapes locally and yet is able to display the entire range of astronomical scales from the Earth's neighborhood to the cosmic microwave background. The conformal nature of the projection, preserving shapes locally, may be of particul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(75 citation statements)
references
References 65 publications
3
71
0
1
Order By: Relevance
“…Observed luminous matter large-scale structures, most notably the >400 Mpc Sloan Great Wall (Gott et al 2005), demonstrate the existence of structure on larger scales than simulations predict (assuming luminous matter traces dark matter). It has also been shown that voids on scales similar to that of the Sloan Great Wall may explain the "cold spots" in the cosmic microwave background (Inoue & Silk 2006).…”
Section: Introductionmentioning
confidence: 75%
“…Observed luminous matter large-scale structures, most notably the >400 Mpc Sloan Great Wall (Gott et al 2005), demonstrate the existence of structure on larger scales than simulations predict (assuming luminous matter traces dark matter). It has also been shown that voids on scales similar to that of the Sloan Great Wall may explain the "cold spots" in the cosmic microwave background (Inoue & Silk 2006).…”
Section: Introductionmentioning
confidence: 75%
“…The low-redshift limit of z 0.04 ensures that the sample is within the Hubble flow, and excludes the Coma and Virgo clusters. Since the SDSS "great wall" spans a redshift range of 0.065 z 0.09 (Gott et al 2005), it is fully contained within the low-redshift range. This allows us to isolate the effect of the "great wall" by comparing the low-redshift range to the high-redshift range.…”
Section: Catalog Datamentioning
confidence: 99%
“…Our numbers may not be precise, but they show the chronological orders and basic parameters of the various important landmarks of the cosmic history. A conformal map of the universe depicting the recent discoveries up to the beginning of this 21th century can be found in [242], which is largely for experts.…”
Section: A Cheat Sheet Of the Cosmo-history And A Map Of The Universementioning
confidence: 99%
“…The criterion for the existence of an event horizon is quite straightforward. From 242) The cosmic event horizon should not be confused with the black hole event horizon, although the two have some similarities. There is also an overall event horizon beyond which no light signal will be able to reach an observer.…”
Section: )mentioning
confidence: 99%